An Investigation of VLF Transmitter Wave Power in the Inner Radiation Belt and Slot Region. Issue 7 (13th July 2019) - Meredith, Nigel P.; Horne, Richard B.; Clilverd, Mark A.; Ross, Johnathan P. J.
Abstract: Signals from man‐made Very Low Frequency (VLF) transmitters, used for communications with submarines, can leak into space and contribute to the dynamics of energetic electrons in the inner radiation belt and slot region. In this study we use ∼5 years of plasma wave data from the Van Allen Probe A satellite to construct new models of the observed wave power from VLF transmitters both as a function of L * and magnetic local time and geographic location. Average power peaks primarily on the nightside of the Earth for the VLF transmitters at low geographic latitudes. At higher latitudes the peak average power extends further in magnetic local time due to more extensive periods of nighttime in the winter months. Nighttime power is typically orders of magnitude more than that observed near noon, implying that loss rates from a given VLF transmitter will also maximize in this region. The observed power from any given VLF transmitter is tightly confined in longitude, with the nightside peak power typically falling by a factor of 10 within 10° longitude of the location of the peak signal. We show that the total average wave power from all VLF transmitters lies in the range 3–9 pT 2 in the region 1.3< L * <3.0, with approximately 50% of this power emanating from three VLF transmitters, NWC, NAA, and DHO38. Key Points: We construct new models of the wave power from VLF transmitters in the inner magnetosphere using wave data from Van Allen probe A The total average wave power from all VLF transmitters lies in the range 3–9 pT 2 in the region 1.3< L * <3.0 Approximately 50% of the total wave power from VLF transmitters in the region 1.3< L * <3.0 comes from the transmitters NWC, NAA, and DHO38